The GLMA handbook on LGBT health - Schneider, Jason S.; Silenzio, Vincent M. B.; Erickson-Schroth, Laura (Praeger, An imprint of ABC-CLIO, LLC, 2019)
This comprehensive review addresses physical, mental, and emotional health, as well as policy decisions affecting the LGBT community from youth through old age.